Characterization of Yellow Pumpkin Seed Skim Milk (Cucurbita moschata) Through Foam-Mat Drying Method - Irmayanti, Irmayanti; Anwar, Chairil; HA, Umar (Jurnal Ilmu Pangan dan Hasil Pertanian, 2022)
Skim milk is nonfat milk powder which is made by drying to remove some of the water and fat contained in it but also does not remove the lactose, protein, minerals, fat-soluble vitamins, and water-soluble vitamins (B12). In the manufacture of skim milk, it is necessary to add a filler that functions to dissolve the material in water and can also facilitate the drying process. The filler selected in this study was maltodextrin. The foam-mat drying method requires a foaming agent to produce foam during processing. The type of foaming agent selected in this study was egg white. The purpose of this research was to determine the best concentration of maltodextrin and foaming agent on the characteristics of pumpkin seed skimmed milk. The research used a completely randomized design (CRD) with a factorial pattern consisting of 3 levels with 2 factors. The first factor was maltodextrin (M) consisting of 3 levels, namely M1 5%, M2 10% and M3 15%. While the second factor was the addition of foaming agent (T) consisting of 3 levels, namely T1 10%, T2 15% and T3 20%. Analysis product consisted of yield, water content, ash content, lipid content and organoleptic (taste and color). The addition of 15% maltodextrin concentration and the addition of 15% foaming agent was the best treatment in this research with a yield of 8.75%, water content 8.38%, ash content 1.59%, lipid content 10.37%, hedonic taste test 4, 13 (like) and color hedonic test 3.65 (like very much).